Characteristics of patients patch tested in the European Surveillance System on Contact Allergies (ESSCA) network, 2009–2012. (13th May 2015) - Uter, Wolfgang; Gefeller, Olaf; Giménez‐Arnau, Ana; Frosch, Peter; Duus Johansen, Jeanne; Schuttelaar, Marie‐Louise; Rustemeyer, Thomas; Larese Filon, Francesca; Dugonik, Aleksandra; Bircher, Andreas; Wilkinson, Mark
Summary Background Patch test results often vary between departments, and also between countries. Such variation may be partly attributable to systematic effects introduced by patient characteristics, differing exposures, patient selection, or methodological differences. Objective To examine the amount of variation of patient characteristics in terms of the MOAHLFA index and of the proportion of patients with at least one positive reaction to the (European) baseline series ('P' measure), and to examine potential reasons for the variation. Methods A retrospective analysis was performed of patch test data from 63 530 consultations collected by 53 departments from 12 countries participating in the European Surveillance System on Contact Allergies (ESSCA) ( www.essca‐dc.org) between 2009 and 2012. Results Considerable variation in the prevalence of the MOAHLFA factors between departments was found, caused, for example, by differing specializations (e.g. occupational dermatology) or patient characteristics. Notable variation concerning the 'P' measure was observed; however, larger national networks (contributing to the ESSCA) tend to have quite similar ranges of this measure. Conclusions Data from one department per country give valuable insights into the spectrum of contact allergy prevalence rates in that country, but are not as representative as national data pooled from several departments.